Analysis of the curricular framework for the Chemistry Licentiate Degree Course at the IFMT through DE - Leão, Marcelo Franco; Del Pino, José Claudio; Oliveira, Eniz Conceição (Revista Linhas, 2019)
The curricular framework for a licentiate degree course has a direct influence on the type of teacher it will be qualifying. Thus, the objective of this study is to analyze the curricular framework for the Chemistry Licentiate Degree Course through DE by the IFMT Cuiabá-Bela Vista Campus in order to verify conformities with the national official documents and to indicate any adjustments for conformance. It is a document analysis from a qualitative approach that took place during 2016 and 2017. It was verified that the current matrix, as proposed in 2012, complies with the total hours required for the supervised internship, for complementary activities, and for practice as a curricular component, however, it does not comply with the 3,200 hours required for a licentiate degree course. It was found that the above matrix includes important and compulsory themes, such as the Brazilian Sign Language, inclusive education, youngster and adult education, and environmental education; but it does not include ethnic-racial issues, for example. One other aspect that was verified is the lack of discussions on the history, epistemology and/or philosophy of science, STS education, and education technologies. Therefore, the curricular framework analyzed complies in part with the national curriculum guidelines but needs some adjustments regarding the total course hours that could be achieved through the insertion of subjects of both specific and pedagogical types. Keywords: Curriculum. Curriculum guidelines. Teacher Training. Legislation.